2006
DOI: 10.1590/s1519-566x2006000600010
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory environment effects on the reproduction and mortality of adult screwworm (Diptera: Calliphoridae)

Abstract: o objetivo de fornecer insetos para programas para sua erradicação, através da técnica do inseto estéril. Novos métodos de criação têm auxiliado na redução dos custos desses programas de erradicação. Nós examinamos o efeito e a interação de três temperaturas (24,5, 29,5 e 34,5 o C), duas dietas (carboidrato e carboidrato + proteína) e três densidades populacionais (300, 400 e 500 moscas/gaiola), na fecundidade eclosão de larvas, número de ovos fertilizados, mortalidade (macho e fêmea) e desenvolvimento dos ová… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 17 publications
0
20
0
2
Order By: Relevance
“…1d) (Berkebile et al, 2006). More important, the mortality rate of eggs (failure to hatch) deposited by females held for 5 days at constant temperatures in the range 23-40 • C (28 dd) increases with temperature ( Fig.…”
Section: The Pbdm Dynamics Modelmentioning
confidence: 92%
“…1d) (Berkebile et al, 2006). More important, the mortality rate of eggs (failure to hatch) deposited by females held for 5 days at constant temperatures in the range 23-40 • C (28 dd) increases with temperature ( Fig.…”
Section: The Pbdm Dynamics Modelmentioning
confidence: 92%
“…In crosses ÔjÕ and Ôk,Õ 30 females were exposed to 1 fertile and 9 sterile males. After 7 d, females were allowed to oviposit on a plate containing ground meat and spent larval diet in a dark room (37ЊC; 80% relative humidity [RH]) for 2 h (Berkebile et al 2006). During the oviposition period, the plates with adult diet were covered to avoid feeding.…”
Section: Methodsmentioning
confidence: 99%
“…The Þrst set (parental crosses) compared intrastrain and reciprocal interstrain crosses (ÔaÕ to ÔdÕ) and the second set (F 1 crosses; ÔeÕ to ÔiÕ) compared four backcrosses to BRA and a BRA intrastrain cross (Table 3). For each cross, 80 couples were placed together for 7 d, after which the females were allowed to oviposit (Berkebile et al 2006). Eggs were separated according to Berkebile and Skoda (2002).…”
Section: Table 2 Competitiveness Indices (Mean ؎ Se) Of Sterile Malementioning
confidence: 99%
“…Studies have shown the influence of temperature on ovarian development and egg laying [6] [7], as well as the interference of physical and nutritional properties of bovine feces on egg production [8] [9] and larval growth [10]- [12].…”
Section: Introductionmentioning
confidence: 99%
“…Commonly described methodologies for obtaining flies in laboratory are manual deposition of eggs onto fecal [9] [11], fresh [6] [19] and lyophilized mass [20]; egg laying by pregnant females directly onto the feces in laboratory [13]; egg storage in pieces of "organza" fabric [16] or filter paper [4] [5] [8] followed by deposition onto fecal plates.…”
Section: Introductionmentioning
confidence: 99%